ДИДАКТИЧНІ УМОВИ ФОРМУВАННЯ ЧИТАЦЬКОЇ САМОСТІЙНОСТІ МОЛОДШИХ ШКОЛЯРІВ (Педагогіка вищої та середньої школи, 2007)
The article deals with the guestion of didactic conditions of the formation of junior pupils reading independence. The content of elementary literary educations consists in developing valuable habits of reading, pupils acguaintance with children's literature in combination of genres, author’s and thematic variety, in artistic — acsthetic perception o f the text and the book.